1991
DOI: 10.1073/pnas.88.10.4255
|View full text |Cite
|
Sign up to set email alerts
|

Transferrin-polycation-DNA complexes: the effect of polycations on the structure of the complex and DNA delivery to cells.

Abstract: We have previously described a gene delivery system based upon the receptor-mediated endocytosis of DNA complexed with transferrin-polycation conjugates. This delivery system has been found to be very effective for both the internalization and the expression of genetic material in cells that have many transferrin receptors. Upon scrutinization of the parameters involved in this method, which we have termed transfeMnfection, we note two important features of the process: the polycation in polycation-transferrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
280
0
3

Year Published

1998
1998
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 477 publications
(300 citation statements)
references
References 10 publications
17
280
0
3
Order By: Relevance
“…Complexes in which poly K was substituted with either 3.5% or 7.8% sulfo-LC SPDP gave efficient transfection. These results are consistent with reports that poly K substituted to a high extent with transferrin moieties condensed DNA into complexes which achieve less gene transduction than less substituted poly K. 6 In contrast, Erbacher and colleagues 16 found that polymers 190 residues in length, substituted at 30-40% with galactose moieties, gave maximal expression intensity in the presence of chloroquine. However, the galactose-substituted polymer differs from our system.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Complexes in which poly K was substituted with either 3.5% or 7.8% sulfo-LC SPDP gave efficient transfection. These results are consistent with reports that poly K substituted to a high extent with transferrin moieties condensed DNA into complexes which achieve less gene transduction than less substituted poly K. 6 In contrast, Erbacher and colleagues 16 found that polymers 190 residues in length, substituted at 30-40% with galactose moieties, gave maximal expression intensity in the presence of chloroquine. However, the galactose-substituted polymer differs from our system.…”
Section: Discussionsupporting
confidence: 90%
“…[1][2][3][4][5][6][7][8][9] A carrier, usually composed of a polycationic protein chemically conjugated to a receptor-specific ligand, is used to condense DNA and present it to the target cell. Careful manipulation of the concentration of NaCl can produce complexes, containing a single plasmid DNA molecule, ranging in size from 10-25 nm in diameter.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular conjugates of poly-lysine with natural or artificial ligands utilise the DNA-binding and -condensing properties of poly-lysine to mediate interaction with DNA (Wagner et al, 1991;Perales et al, 1994). Upon formation of a DNA-poly-lysine-ligand complex (polyplex (Felgner et al, 1997)), gene transfer is facilitated via receptor-mediated endocytosis.…”
mentioning
confidence: 99%
“…To avoid degradation by the endocytic pathway and to facilitate fusion with the cell membrane, fusion proteins derived from Sendai virus have been incorporated into liposomes. 110,111 To facilitate cytoplasmic transit to the cell nucleus, high mobility group proteins with nuclear localization signals have been complexed to the DNA. 112,113 Most recently, elements from Epstein-Barr virus (oriP and EBNA-1) have been included in the DNA within liposomes to prolong the retention of transgenes in dividing cells.…”
Section: Lentivirus Vectorsmentioning
confidence: 99%